Effects of multifaceted optimization management for chronic heart failure: a multicentre, randomized controlled study. (30th September 2022) - Pan, Guangming; Ji, Weiqiang; Wang, Xia; Li, Song; Zheng, Chaoyang; Lyu, Weihui; Feng, Xiaoyan; Xia, Yu; Xiong, Zhihua; Shan, Haohong; Yang, Haiyu; Zou, Xu
Abstract: Aims: In recent years, we have developed the concept of 'clinical pathway based on integrated traditional Chinese and western medicine for the management of Chronic heart failure (CHF)'. The purpose of this study was to assess the implementation effects of multifaceted optimization management of chronic heart failure. Methods: A total of nine physicians in optimization group from nine research sites received multifaceted intervention (a 1‐day training session on how to implement the optimization programme, a written optimization programme for CHF management, supervision from daily quality coordinator, and 1‐monthly monitoring and feedback of performance measure) with respect to the management of CHF, comparing to nine physicians in control group who did not receive the aforementioned multifaceted intervention and diagnosed and treated CHF patients with conventional programme (usual care). After that, a total of 256 patients with CHF were enrolled and randomly assigned to receive optimization programme [integration of usual care and traditional Chinese medicine (TCM) treatment] or conventional programme (usual care) for the treatment of CHF. The primary outcome was the change in New York Heart Association (NYHA) functional classification during 24 weeks of treatment. Results: When compared with usual care, multifaceted optimization management resulted in superior improvements in NYHA functional classification at the 12‐week visit ( P  = 0.023), the 16‐week, 20‐week, and 24‐week visits ( P  < 0.001). It also demonstrated superior performance in comparison with the conventional programme with respect to readmission rate for major adverse cardiovascular events (MACEs), readmission rate for worsening heart failure, plasma N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) level, left ventricular ejection fraction (LVEF), patient TCM syndrome scores, quality of life, and patients with heart failure with reduced ejection fraction (HFrEF) in optimization group more likely received beta‐blockers and ACE inhibitors or ARBs than those in control group ( P  = 0.038 and P  = 0.013, respectively). Conclusions: It is likely that the multifaceted optimization programme used in this study is feasible would benefit patients with CHF in NYHA functional classification, readmission for worsening heart failure, plasma NT‐proBNP level, LVEF, patient TCM syndrome scores, and quality of life. Additionally, it would improve hospital personnel adherence to evidence‐based performance measures for HFrEF.